Oxford studies in philosophy of law. Volume 3 - Gardner, John, 1965-2019; Green, Leslie; Leiter, Brian (Oxford : Oxford University Press, 2018)
'Oxford Studies in the Philosophy of Law' is a forum for new philosophical work on law. The essays range widely over general jurisprudence (the nature of law, adjudication, and legal reasoning), philosophical foundations of specific areas of law (from criminal to international law), and other philosophical topics relating to legal theory.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 21, 2018).
Keywords: Law -- Philosophy; Law; Jurisprudence & general issues